Percepción de los estudiantes de enfermería sobre el uso de la simulación clínica en el proceso de aprendizaje - Cuenca Caraguay, Flor Maria (2024)
The clinical simulation in the training process of future health professionals plays a crucial role in the learning process, which allows them to acquire new behaviors from the lived experiences, through active, reflective, pragmatic, theoretical and constructivist learning. Among the objectives was to specify the use of clinical simulators available at the National University of Loja for the learning development of nursing students, as well as to detail the contribution that simulators provide to the learning process of nursing students, a descriptive field study. For this purpose, a mixed approach was used, with a non-experimental-transversal design, by means of an interview and a survey. We had a population of 124 nursing students from the third to seventh cycle of the National University of Loja. Of the 52 students surveyed, 98.1% had practiced in the clinical simulators, and 59.6% agreed with the experience lived in them, because it allowed them to make mistakes and rectify them, with the objective of not making them in real life. They also stated that it helped them to improve both technical and communication skills, 86.5% have experienced improvements in technical skills, because 100% stated that it is an effective tool for learning nursing, so it is necessary that the other students continue to use the simulators, always with the reinforcement of the teachers, because they are the ones who have reinforced their doubts, as stated by the interviewees. It was concluded that the students surveyed and interviewed perceived that clinical simulation facilitates their learning by allowing them to develop skills and acquire abilities. Keywords: perception; training; clinical simulation; mannequin; fidelity.